Discovery of mcr-1-Mediated Colistin Resistance in a Highly Virulent Escherichia coli Lineage - Brian M. Forde (American Society for Microbiology, 2018)
ABSTRACT Resistance to last-line polymyxins mediated by the plasmid-borne mobile colistin resistance gene (mcr-1) represents a new threat to global human health. Here we present the complete genome sequence of an mcr-1-positive multidrug-resistant Escherichia coli strain (MS8345). We show that MS8345 belongs to serotype O2:K1:H4, has a large 241,164-bp IncHI2 plasmid that carries 15 other antibiotic resistance genes (including the extended-spectrum β-lactamase blaCTX-M-1) and 3 putative multidrug efflux systems, and contains 14 chromosomally encoded antibiotic resistance genes. MS8345 also carries a large ColV-like virulence plasmid that has been associated with E. coli bacteremia. Whole-genome phylogeny revealed that MS8345 clusters within a discrete clade in the sequence type 95 (ST95) lineage, and MS8345 is very closely related to the highly virulent O45:K1:H4 clone associated with neonatal meningitis. Overall, the acquisition of a plasmid carrying resistance to colistin and multiple other antibiotics in this virulent E. coli lineage is concerning and might herald an era where the empirical treatment of ST95 infections becomes increasingly more difficult. IMPORTANCE Escherichia coli ST95 is a globally disseminated clone frequently associated with bloodstream infections and neonatal meningitis. However, the ST95 lineage is defined by low levels of drug resistance amongst clinical isolates, which normally provides for uncomplicated treatment options. Here, we provide the first detailed genomic analysis of an E. coli ST95 isolate that has both high virulence potential and resistance to multiple antibiotics. Using the genome, we predicted its virulence and antibiotic resistance mechanisms, which include resistance to last-line antibiotics mediated by the plasmid-borne mcr-1 gene. Finding an ST95 isolate resistant to nearly all antibiotics that also has a high virulence potential is of major clinical importance and underscores the need to monitor new and emerging trends in antibiotic resistance development in this important global lineage.